EXPLORING THE MENTAL PROCESSES INVOLVED IN READING COMPREHENSION, INCLUDING SCHEMA THEORY, MATACOGNITION, AND THE INFLUENCE OF BACKGROUND KNOWLEDGE. ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an overview of the development of reading comprehension research, emphasizing studies from the last fifteen years compared to those from the preceding decades. The author discusses the historical evolution of reading comprehension research, from early interest in holistic mental processes in the early 20th century to the dominance of behaviorism. The renewed interest in reading comprehension explores the interaction of learner characteristics (background knowledge, vocabulary, metacognitive skills), text structures (narrative and expository), and social contexts. The article highlights schema theory's role in understanding comprehension and acknowledges the gaps between current research and teaching practices.